Telecommunication Numbering System Roadmap towards Next Generation Network Era in Indonesia - Maman Abdurohman; Bambang Setia Nugroho; Aji Gautama Putrada (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The telecommunication numbering system in Indonesia currently complies to the International TelecommunicationUnion (ITU) standard, that is ITU-T E.164. In accordance to both technology development and the growing of network users, ITU has also been designing future infrastructure network concept, namely Next Generation Network Infrastructure (NGNI). In its technical paper, ITU discusses future generation’s specification as well as current network migration scenarios towards Next Gereration Network (NGN) in developing countries and its impact on regulations, business processes, and the numbering system. The scenario described in the concept is yet universal and the implementation would be highly depending on the conditions of ones country. This paper proposes the roadmap of numbering system from the current state into NGN numbering for the case of Indonesia. The method used in this paper are benchmarking with several countries that have started with the transformation process, forecasting with regression method based on the existing trends and descriptive analysis. This paper has proposed the stages of numbering roadmap towards NGN numbering system, the achievement parameters, and the indicators that are suitable for Indonesia.